Antimicrobial Susceptibility Pattern of Methicillin-Resistant Staphylococcus aureus in a Tertiary care Hospital - Aqsa Aslam; Wajiha Mahjabeen; Muhammad Zia ul Rehman; Sana Qanber Abbasi; Nazish Babar; Huzaifa Saleem (Journal of University Medical & Dental College, 2022)
Background & Objective: Methicillin-resistant Staphylococcus aureus (MRSA) has become a major therapeutic issue across the world. The current study is designed to evaluate the trends in the susceptibility pattern of MRSA strains isolated from various clinical samples in a tertiary care hospital in Islamabad. The antimicrobial susceptibility pattern will not only add data but will also guide us about treatment options for MRSA infection.